High-Speed Fault Identification and Protection for HVDC Line Using Wavelet Technique - Herold, Gerhard; Jäger, Johann; et al. (2001 IEEE Porto Power Tech, 2001)
This paper describes a new high-speed HVDC line protection using wavelet technique. Based on the representation of the tavelling waves through wavelet modulus maxima, the protection criterions for HVDC line are proposed. Simulations are carried out for testing the criterions. And the influences of similar faults are discussed. The protection can detect the HVDC line fault well and identify the HVDC line fault clearly from the similar transients, such as commutation failure and AC single phase fault. © 2001 IEEE.
UnivIS-Import:2015-04-16:Pub.2001.tech.IE.leen.highsp_6
Keywords: edge detection; HVDC fault; HVDC line; identification; protection; wavelet; wavelet modulus maxima